Effect of long-term isometric training on core/torso stiffness - Lee, B. C. Y.; McGill, S. M. (The Journal of Strength and Conditioning Research, 2015)
Although core stiffness enhances athletic performance traits, controversy exists regarding the effectiveness of isometric vs. dynamic core training methods. This study aimed to determine whether long-term changes in stiffness can be trained, and if so, what is the most effective method. Twenty-four healthy male subjects (23 ± 3 years; 1.8 ± 0.06 m; 77.5 ± 10.8 kg) were recruited for passive and active stiffness measurements before and after a 6-week core training intervention. Twelve subjects (22 ± 2 years; 1.8 ± 0.08 m; 78.3 ± 12.3 kg) were considered naive to physical and core exercise. The other 12 subjects (24 ± 3 years; 1.8 ± 0.05 m; 76.8 ± 9.7 kg) were Muay Thai athletes (savvy). A repeated-measures design compared core training methods (isometric vs. dynamic, with a control group) and subject training experience (naive vs. savvy) before and after a 6-week training period. Passive stiffness was assessed on a "frictionless" bending apparatus and active stiffness assessed through a quick release mechanism. Passive stiffness increased after the isometric training protocol. Dynamic training produced a smaller effect, and as expected, there was no change in the control group. Active stiffness did not change in any group. Comparisons between subject and training groups did not reveal any interactions. Thus, an isometric training approach was superior in terms of enhancing core stiffness. This is important since increased core stiffness enhances load bearing ability, arrests painful vertebral micromovements, and enhances ballistic distal limb movement. This may explain the efficacy reported for back and knee injury reduction.